2002
DOI: 10.1191/0309133302pp352ra
|View full text |Cite
|
Sign up to set email alerts
|

Recent research on the nature, origin and climatic relations of blocky and stratified slope deposits

Abstract: A selection of subaerial slope processes is discussed together with the morphological and sedimentological traces that are left by the processes. Emphasis is on mass transfers related to (coarse) blocky slopes and to scree accumulations, either on steep or on gentle slopes. New developments in the interpretation of more or less clearly stratified slope deposits are discussed in the light of the findings of research focusing on present-day process-form (process-material) relationships. The question of the clima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 108 publications
2
36
0
Order By: Relevance
“…Stratification and a clear sorted structure are indicative of an overland flow component [15]. The repeatable pattern of switches between matrix-rich gravel and layers of coarser clast-rich gravel is characteristic of stratified slope deposits, formed through multiple stacked grain flows [88]. Clast form data support this interpretation, with the highest C40 and RA values reported from this study.…”
Section: Lfa4supporting
confidence: 75%
See 1 more Smart Citation
“…Stratification and a clear sorted structure are indicative of an overland flow component [15]. The repeatable pattern of switches between matrix-rich gravel and layers of coarser clast-rich gravel is characteristic of stratified slope deposits, formed through multiple stacked grain flows [88]. Clast form data support this interpretation, with the highest C40 and RA values reported from this study.…”
Section: Lfa4supporting
confidence: 75%
“…11). Such high angularity is characteristic of slope deposits, with a relatively short, passive transport pathway [2,87,88]. These data suggest a preference to slabby, elongate forms, also indicative of unmodified, frost-weathered clast [2].…”
Section: Lfa4mentioning
confidence: 78%
“…Stratified talus slopes are generally due to an alternation of different processes and/or changes in intensity of rockfall generation (e.g. Francou, 1988;van Steijn et al 2002;Sass and Krautblatter, 2007), with layers of angular rock fragments embedded in a finer matrix alternating with layers of equally angular material with an openwork structure. For Sass and Krautblatter (2007), in warm temperate conditions this alternation may correspond to climatic oscillations during the Lateglacial and the Holocene, with an important delivery of coarse debris in cold periods of freeze-thaw activity (e.g.…”
Section: Talus Slope Structurementioning
confidence: 99%
“…Several geomorphological and sedimentological studies have focused on their morphology, structure and origin (e.g. Francou, 1988;van Steijn et al, 2002;Sass, 2006), but little research has focused on the permafrost distribution and stratigraphy within talus slopes (e.g. Lütschg et al, 2004;Lambiel and Pieracci, 2008;Phillips et al, 2009) or on the palaeoclimatic significance of their ice content (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This term is used within this thesis as a collective description for the entire range of clast supported periglacial boulder deposits. While block deposits are generally considered to be indicators of past periglacial conditions, there has been significant literature (Van Steijn et al 2002, Andrè 2003, Andrè et al 2008) that have suggested that they are of polygenetic origin and may have developed at least in part under deep chemical weathering during Tertiary and interstadial warm periods of the Quaternary (Rea et al 1997, Andrè et al 2008. The widespread evidence for clay weathering products and rounded nature of boulders associated with some block deposits, do suggest that block deposits in part owe their formation to chemical weathering (Caine 1983, Rea et al 1997.…”
Section: Block Depositsmentioning
confidence: 99%